THE ROLE OF C-METHYL-4,10,16,22-TETRAMETOXY CALIX[4]ARENE AS INHIBITOR OF CALCIUM CARBONATE (CaCO3) SCALE FORMATION - Suharso Suharso; Buhani Buhani; Tati Suhartati (Universitas Gadjah Mada, 2009)
The role of C-methyl-4,10,16,22-tetrametoxy calix[4]arene as inhibitor of calcium carbonate scale formation has been investigated. The result shows that C-methyl-4,10,16,22-tetrametoxy calix[4]arene inhibits a formation of calcium carbobate crystals at a concentration of growth solution of 0.1 M. The ability of C-methyl-4,10,16,22-tetrametoxy calix[4]arene as inhibitor of the formation of calcium carbobate scale is 33-100% in inhibiting growth rate of CaCO3 scale formation. This ability depends on the concentration of C-methyl-4,10,16,22-tetrametoxy calix[4]arene added into growth solution. However, the addition of C-methyl-4,10,16,22-tetrametoxy calix[4]arene at a range of 10-100 ppm is a much enough in inhibiting the growth rate of CaCO3 crystals.